Effect of entrepreneurial and market orientation on consumer engagement and performance of manufacturing SMEs. Issue 1 (15th January 2018) - Mamun, Abdullah Al; Mohiuddin, Muhammad; Fazal, Syed Ali; Ahmad, Ghazali Bin
Abstract : Purpose: This study aims to examine the effect of entrepreneurial and market orientations on consumer engagement and the performance of manufacturing small- and medium-sized enterprises (SMEs) under the premise of the resource-based view (RBV) theory. Design/methodology/approach: This study adopts a cross-sectional design, and quantitative data were collected from 360 manufacturing SMEs in Peninsular Malaysia. SMEs were selected using a stratified multi-stage sampling method from a total of 37, 861 manufacturing SMEs. The respondents were selected from Selangor, Johor, Penang, Perak, Kelantan and Terengganu, as these states make up the majority (79 per cent) of the manufacturing SMEs in Malaysia. Findings: Entrepreneurial and market orientations have statistically significant positive effects on consumer engagement. Consumer engagement in turn positively affects the performance of manufacturing SMEs in Peninsular Malaysia. Findings also revealed a partial mediation of consumer engagement between entrepreneurial and market orientations on performance. Research limitations/implications: A larger sample size may improve the generalizability of the findings. Managers may be able to apply the findings of this paper in developing strategies for their manufacturing SMEs, specifically, by focusing on entrepreneurial and market orientation to raise consumer engagement and to improve the overall performances of their SMEs. Originality/value: This study focuses on manufacturing SMEs in Malaysia, an emerging country with conditions unique to other industrialized countries. This study aims to demonstrate that integrated entrepreneurial and market orientations have significant effects on SMEs' performance. This relationship could be mediated by consumer engagement. Specifically, consumer orientation may influence the effect of entrepreneurial and market orientations on overall firm performance..